2018
DOI: 10.3892/or.2018.6731
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib improves adoptive carbonic anhydrase�IX‑specific chimeric antigen receptor‑modified NK92 cell therapy in mouse models of human renal cell carcinoma

Abstract: Adoptive chimeric antigen receptor (CAR) T or NK cells offer new options for cancer treatment. Clinical results indicate that CAR-modified T cell (CAR-T) therapy has curative therapeutic efficacy for hematological malignancies. However, the efficacy of the therapy in most solid tumors, including advanced renal cell carcinoma (RCC), remains highly limited. New regimens, including combination of CART cells with chemical drugs, must be studied to enhance the therapeutic efficacy of CART or NK cells for solid tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In vitro consideration indicated that CAR-NK92 had a remarkable cytotoxic effect on target cells. Furthermore, a combination of bortezomib with CAR-NK92 cells showed greater suppressive efficacy against CAIX-positive tumor xenografts in comparison to the monotherapy with either CAR-NK92 cells or bortezomib [161].…”
Section: Preclinical Studies On Solid Tumorsmentioning
confidence: 93%
See 1 more Smart Citation
“…In vitro consideration indicated that CAR-NK92 had a remarkable cytotoxic effect on target cells. Furthermore, a combination of bortezomib with CAR-NK92 cells showed greater suppressive efficacy against CAIX-positive tumor xenografts in comparison to the monotherapy with either CAR-NK92 cells or bortezomib [161].…”
Section: Preclinical Studies On Solid Tumorsmentioning
confidence: 93%
“…Unchanged NK-92 cells failed to inhibit tumor progression [153,160]. Advanced renal cell carcinoma (RCC) is another solid tumor that has been evaluated with antigenspecific CAR-NK cells [161]. In this regard, a carbonic anhydrase IX (CAIX)-specific third-generation CAR-NK92 cells were utilized.…”
Section: Preclinical Studies On Solid Tumorsmentioning
confidence: 99%
“…Many attempts have been made to enhance CAR T cell activity by using small molecules. Several studies have shown the synergy effects of small molecules, including tyrosine kinase inhibitors, cytotoxic agents, histone deacetylase inhibitors, proteasome inhibitors, and immune-modulators, with CAR T cells (Table 2) [191][192][193][194][195][196][197][198]. Afatinib, a tyrosine kinase inhibitor, increased CAR-NK cell infiltration into the tumor [192].…”
Section: Synergistic Effects Of Car T Cell Therapy With Compounds 41 Compounds Enhancing Car T Cell Activitymentioning
confidence: 99%
“…This point is key to ensure the safety of these off the shelf approaches based on cell lines, as is the case for NK-92 derived cell products. Importantly, recent reports showed that CAR-expressing NK-92 cells can be used in combination with drugs like bortezomib [ 90 ] or regorafenib [ 91 ] or in combination with oncolytic virus [ 92 ] to improve responses in solid tumor models. These results led to several clinical trials using CAR-expressing NK-92 cells for patients with CD33 + AML (acute myeloid leukemia, Identifier: NCT02944162), CD19 + ( Identifier: NCT02892695) or CD7 + ( Identifier: NCT02742727) leukemia/lymphoma and Her2 + glioblastoma ( Identifier: NCT03383978).…”
Section: Alternatives To Primary T Cellsmentioning
confidence: 99%